Dyslogic syndrome why millions of kids are "hyper," attention-disordered, learning disabled, depressed, aggressive, defiant, or violent - and what we can do about it - Rimland, Bernard, 1928-2006. (London ; Philadelphia : Jessica Kingsley Publishers, 2008)
Dyslogical children are commonly labelled as having one or more of a mix of conditions that includes bipolar disorder, attention deficit/hyperactivity disorder, and oppositional defiant disorder. This text outlines the impact of biological factors on children, examining the influences of toxins and dietary deficiencies.
Overview : what is'dyslogic?' -- The dyslogic epidemic's victims : America's'mad,''bad,' and'dumbed down' children -- Why'nurture' fixes can't cure dyslogic -- Why drugs don't cure dyslogic -- Dietary dyslogic : why what your kids eat (or don't eat) can make them crazy, sad, or violent -- The contaminated brain : how our toxic environment affects our children's thinking -- Medically caused dyslogic : when drugs and other medical treatments damage the brain -- Why no dyslogic child is'hopeless' -- An action plan for ending dyslogic.
Description based on print version record.
Includes bibliographical references and indexes.
Keywords: Behavior disorders in children -- Environmental aspects; Behavior disorders in children -- Nutritional aspects; Behavior disorders in children -- Physiological aspects; Neurotoxicology; Behavioral toxicology; Child Behavior Disorders -- etiology; Child Behavior -- physiology; Child Nutritional Physiology Phenomena; Child; Environmental Exposure -- adverse effects; Nervous system -- Drug effects; Electronic books; Electronic books